An Analytical study on Male Mammography - Jamil Sheik; Dr Ramgopal (Asian Journal of Medical Radiological Research, 2018)
Background: Mammography of male breast accounts for less than 1.5% of mammographic examinations done in breast imaging centers. In females the awareness of breast cancer is very high when compare to males. Females will undergo periodical screening very frequently through, mammography or clinical examination. The most common presenting symptoms and signs that led to a request for mammogram in these men include an enlargement of breast, a palpable lump, and breast tenderness (1). Aim and study: To know the breast lesions in males through mammography. Subjects and Methods: we have examined breast of 50 Males with the help of mammography. Results: Out of 50 patients. Gynaecomastia is seen in 18 patients. Breast cancer is seen in 4 patients. Conclusion: Routine mammography is very much useful in females for screening of breast cancer. In males also it is useful in ruling out different breast lesions like Gynaecomastia, breast cancer.